STUDI PENERAPAN STANDAR KOMPETENSI LULUSAN PENDIDIKAN DASAR DAN PERMASALAHANNYA - Ananda, Rizki; Huriyah Putri, Alfira; Safitri, Nofita; Refinta, Yona; Assidiqie MB, Ega (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The implementation of the Graduate Competency Standards (GCS) at theelementary education level is a key indicator in assessing the success of theeducational process. The GCS includes aspects of attitude, knowledge, and skillsexpected to be possessed by every graduate as the final outcome of learning.However, the implementation of GCS in primary education often faces variouschallenges, both internal—such as teacher quality and teaching methods—andexternal—such as limited infrastructure and parental support. This study aims toanalyze the extent to which GCS is implemented in elementary schools and toidentify the problems hindering its achievement. The research employed adescriptive qualitative method with a case study approach in several urban and ruralelementary schools. The results indicate that teachers' understanding of GCSremains uneven, and instructional practices are not yet fully aligned with theexpected competency outcomes. These findings suggest the need for strongerteacher training, more consistent policy support, and collaboration among schools,families, and communities to optimize the achievement of GCS in basic education.